Differential expression of transcription factors NF-κB and STAT3 in periodontal ligament fibroblasts and gingiva of healthy and diseased individuals. (October 2017) - Ambili, R.; Janam, Presanthila; Saneesh Babu, P.S.; Prasad, Manu; Vinod, D.; Anil Kumar, P.R.; Kumary, T.V.; Asha Nair, S.
Highlights: Higher activation of NF-κB and STAT3 in diseased than healthy gingiva. Higher activation of NF-κB and STAT3 in PDLF from diseased than healthy tissue. Differential expression of NF-κB and STAT3 in diseased PDLF upon LPS challenge. Abstract: Objective: Pathogens and host mediators can activate transcription factors in periodontal cells to bring about gene level alterations, thereby accentuating the periodontal disease process. Nuclear factor-kappa B (NF-κB) and signal transducers and activators of transcription 3 (STAT3) are two pivotal transcription factors implicated in chronic inflammatory diseases. But their importance in periodontal pathogenesis has not been investigated in detail. The aim of the present study was to evaluate the expression of activated transcription factors and their target genes in healthy and diseased periodontium. Design: Primary culture of periodontal ligament fibroblasts (PDLF) were established from healthy and diseased periodontium using explant culture methods. NF-κB and STAT3 activation in these cells by Porphyromonas gingivalis LPS (lipopolysaccharide) was demonstrated using confocal microscopy and mRNA expression of target genes were evaluated by quantitative real time PCR. NF-κB and STAT3 expression in diseased and healthy gingival tissues were analyzed using immunohistochemistry. Results: A basal upregulation of transcription factors and their target genes were noted in diseased PDLF compared to healthy ones. LPS challenge induced differential expression of NF-κB and STAT3 and their target genes in diseased PDLF compared to healthy ones. Immunohistochemical analysis revealed significant activation of transcription factors in diseased gingival tissues. Conclusion: The findings of the present study reveal the role of transcription factors NF-κB and STAT3 in periodontal pathogenesis and disease susceptibility of fibroblast subpopulations in periodontal disease could be mediated through activation of NF-κB and STAT3. Since genetic factors are nonmodifyable, transcription factors are promising targets for future host modulation therapy.